The Letters of John of Dalyatha/Hymns of Saint Ephrem the Syrian/Saint John Cassian on Prayer - Plekon, Michael (Cistercian studies quarterly, 2007)
The article reviews several books including "The Letters of John of Dalyatha" and "Hymns of Saint Ephrem the Syrian," translated by Mary Hansbury and "Saint John Cassian on Prayer," translated by A. M. Casiday.